Integration of Intercultural Communicative Competence (ICC) in English Teaching at Bangsri Islamic Boarding School - Muhammad Alvin Rahmawan; Muh Shofiyuddin (LP. Ma'arif Janggan Magetan, 2025)
English language teaching in Islamic boarding schools must integrate intercultural communication to prepare students for global interactions while preserving their cultural and religious identity. Research on Intercultural Communication Competence (ICC) in faith-based and rural contexts remains limited. Therefore, this study examines the integration of ICC in English Language Teaching (ELT) at an Indonesian Islamic boarding school. Using a qualitative case study approach, data was collected through classroom observations, semi-structured interviews, student journals, and document analysis. The research explored how teachers implemented ICC strategies, the challenges encountered, and students’ perceptions. Findings revealed that teachers employed translanguaging, digital media, and linguistic–cultural interlinking to foster ICC, effectively bridging cultural gaps. Teachers showed high consistency in cultural discussions (mean observation score of 4.2/5.0). However, pronunciation difficulties, students’ shyness, grammatical errors, and socio-cultural rivalries were found to hinder ICC development. While students demonstrated strong respect and politeness (self-assessment scores up to 4.5), their active participation and comfort in intercultural interactions remained only moderate (scores around 3.5). These results highlight the urgent need for context-sensitive pedagogical approaches, such as targeted pronunciation exercises and confidence-building activities to enhance ICC while respecting student values. This study contributes to understanding ICC in multilingual, faith-based contexts and offers practical insights for similar educational environments.